FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENGGUNAAN FINTECH PADA UMKM DI KOTA BANDA ACEH MENGGUNAKAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Sultan Rivaldi; Dinaroe Dinaroe (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
Information technology is developing quite rapidly in the financial sector. Financial Technology (FinTech) offers many benefits so the adoption rate is very high at the individual to organizational level. In Indonesia, the implementation of FinTech is quite high because basically FinTech offers great benefits and conveniences. However, amid the high implementation of FinTech at the individual level and large business entities, the use of FinTech in MSMEs is still very low. This study aims to determine what factors influence the interest of MSME to use FinTech services using the Technology Acceptance Model (TAM) theoretical approach by adding a trust factor. The population of this research is all MSMEs in Banda Aceh City. The questionnaires were distributed directly and indirectly (online) from July 24 to August 27, 2021 using the Lemeshow sampling technique, a sample size of 130 was obtained. The research questionnaire data was then analyzed using the Structural Equation Modeling (SEM) method with the help of the SmartPLS 3.3.3 software. The results of data analysis show that perceived usefulness, perceived ease of use, and subjective norms have a positive and significant effect on behavioral intention to use FinTech in MSMEs. Meanwhile, the trust factor does not affect the interest in using FinTech in MSMEs.